2018
DOI: 10.1007/s00586-018-5521-4
|View full text |Cite
|
Sign up to set email alerts
|

Full endoscopic lumbar interbody fusion (FELIF): technical note

Abstract: FELIF is a safe and effective interbody fusion option to decompress the lumbar exiting nerve root and ventral side of dura directly with minimal invasive situation. These slides can be retrieved under Electronic Supplementary Material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 11 publications
0
41
0
1
Order By: Relevance
“…can be used as a viable complement for spinal dysraphisms, degenerative and neoplastic spinal pathologies, including tethered cord, minimally invasive interbody fusion, and surgery for intradural tumors. [38][39][40] The major drawback of designing a single centre clinical trial with strict inclusion and exclusion criteria is that such research approach necessarily narrows down the number of potential candidates at time of patient selection. Additionally, if eligible patients prefer not to be enrolled and opt instead for what is considered to be the standard of care, then it is difficult to rule out the influence of a possible selection bias on the results obtained in both the treatment and control arms.…”
Section: Discussionmentioning
confidence: 99%
“…can be used as a viable complement for spinal dysraphisms, degenerative and neoplastic spinal pathologies, including tethered cord, minimally invasive interbody fusion, and surgery for intradural tumors. [38][39][40] The major drawback of designing a single centre clinical trial with strict inclusion and exclusion criteria is that such research approach necessarily narrows down the number of potential candidates at time of patient selection. Additionally, if eligible patients prefer not to be enrolled and opt instead for what is considered to be the standard of care, then it is difficult to rule out the influence of a possible selection bias on the results obtained in both the treatment and control arms.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting smaller incision, minor trauma, and faster recovery have attracted the attention of spine surgeons. The surgical procedure includes a percutaneous puncture to locate the target segment, step‐by‐step expansion, placement of the operation channel for decompression, endplate preparation, implantation of the interbody cage, and fixation of a percutaneous pedicle screw. This surgical approach reduces the damage to the posterior spinal canal, making it less traumatic than traditional open surgery, with less bleeding, faster postoperative recovery, and a shorter hospital stay.…”
Section: Introductionmentioning
confidence: 99%
“…The cage was then introduced into the intervertebral disc space. Youn MS et al [13] reported a full endoscopic lumbar interbody fusion (FELIF). They used a beveled working cannula (13.7 mm outer diameter, 10.2 mm inner diameter) and an endoscope (10 mm outer diameter, 6 mm working channel, and 15° view angle) to carry out an endoscopic partial facetectomy of the superior articular process with su cient decompression and proper endplate preparation.…”
Section: Discussionmentioning
confidence: 99%